(untitled) (Baghdad Science Journal, 2020)
Mycobacterium tuberculosis resistance to rifampicin is mainly mediated through mutations in the rpoB gene. The effects of rpoB mutations are relieved by secondary mutations in rpoA or rpoC genes. This study aims to identify mutations in rpoB, rpoA, and rpoC genes of Mycobacterium tuberculosis isolates and clarify their contribution to rifampicin resistance. Seventy isolates were identified by acid-fast bacilli smear, Genexpert assay, and growth on Lowenstein Jensen medium. Drug susceptibility, testing was performed by the proportional method. DNA extraction, PCR, and sequencing were accomplished for the entire rpoA, rpoB, and rpoC genes. Twenty-three isolates (32.85%) showed resistance to rifampicin by either proportion method or Genexpert assay. Sequence analysis of the rpoB gene revealed fourteen different mutation patterns. Inside the rifampicin resistance determining region (RRDR), codons: S531L, D516V were highly mutated with frequencies of (21.73%, 17.39%) respectively. Outside the RRDR, there were nine different types of mutations, and M479L was the most prevalent one. Out of 23 RIF resistant isolates, seven isolates (30.43%) carried mutations in the rpoA gene, and twelve isolates (52.17%) harbored a mutation in rpoC. Most of the mutations were identified for the first time in this study. The current study demonstrated that mutations in rpoB, rpoA, and rpoC contributed to RIF resistance in Mycobacterium tuberculosis and this new finding may be relevant to realize how compensatory mutations in the rpoA and rpoC genes restore the fitness cost caused by rifampin resistance-conferring mutations in rpoB.